2020
DOI: 10.1111/ped.14103
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic piperacillin administration in pediatric patients with solid tumors following different intensities of chemotherapy

Abstract: Background Prophylactic antibiotics decrease mortality and morbidity in patients with hematological malignancies following intensive chemotherapy. However, the efficacy of prophylactic antibiotics for pediatric patients with solid tumors remains unclear. Methods We retrospectively assessed 103 neutropenic periods from 26 patients with neuroblastoma or brain tumors following three different intensity chemotherapy regimens (05A3, A, and B). While piperacillin was intravenously administered as prophylaxis (PIPC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…80 Although the incidence of fever in pediatric FNHTR is not yet fully understood, in pediatric hematology and oncology practices, FNHTR require differential diagnosis from infectious diseases such as febrile neutropenia or neoplastic fever. 81,82 In one study, severity of ATR and FNHTR did not change depending on the occurrence time of ATR or FNHTR, and there was no difference in severity depending on the causative blood products. 27 It may not therefore be easy to predict the severity of ATR and FNHTR based only the clinical situation in which actual blood transfusions are performed.…”
Section: Analysis Of the Severity Of Tars (Focused On Atr / Fnhtr) Inmentioning
confidence: 95%
See 1 more Smart Citation
“…80 Although the incidence of fever in pediatric FNHTR is not yet fully understood, in pediatric hematology and oncology practices, FNHTR require differential diagnosis from infectious diseases such as febrile neutropenia or neoplastic fever. 81,82 In one study, severity of ATR and FNHTR did not change depending on the occurrence time of ATR or FNHTR, and there was no difference in severity depending on the causative blood products. 27 It may not therefore be easy to predict the severity of ATR and FNHTR based only the clinical situation in which actual blood transfusions are performed.…”
Section: Analysis Of the Severity Of Tars (Focused On Atr / Fnhtr) Inmentioning
confidence: 95%
“…It has been reported that there is a certain percentage of FNHTR cases that involve high temperature in adults 80 . Although the incidence of fever in pediatric FNHTR is not yet fully understood, in pediatric hematology and oncology practices, FNHTR require differential diagnosis from infectious diseases such as febrile neutropenia or neoplastic fever 81,82 . In one study, severity of ATR and FNHTR did not change depending on the occurrence time of ATR or FNHTR, and there was no difference in severity depending on the causative blood products 27 .…”
Section: Analysis Of the Severity Of Tars (Focused On Atr / Fnhtr) In...mentioning
confidence: 97%
“…Piperacillin (PRL) is a significant third‐generation semi‐synthetic antibiotic with broad spectrum, low toxicity, and strong bactericidal effect 1–4 . It has been widely used to treat various infections caused by Pseudomonas aeruginosa and sensitive gram‐negative bacilli, such as respiratory tract infections, sepsis, and skin infections 5–7 . In the current industrial production, as shown in Figure 1, PRL is mainly synthesized via the ampicillin (AMP) chloride method 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…While some neuroblastomas occurring in infants younger than 18 months spontaneously regress, high-risk neuroblastomas continue to result in poor prognosis even when treated with various chemotherapeutic agents and hematopoietic stem cell transplants after high-dose chemotherapy [3,4]. Chemotherapy for high-risk neuroblastoma usually causes severe myelosuppression due to repeated intensive regimens [4,5].…”
Section: Introductionmentioning
confidence: 99%